(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article describes mathematical formulas and theoretical analysis methods for determining and preventing malfunctions of measuring devices. In selectivity studies, the effects of possible halal components are usually investigated by adding these substances to both blanks and working samples and observing the response. The obtained results are usually used to calculate the actual halal effects